Antecedents factors in customer loyalty among depositors in Tabung Haji Malaysia in Selangor - Nur Fara Anisa Mustaffa Kamal; Nur Farhana Nor Umara; Nur Fatihah Abdullah; Nur Fatihah Najah Muhammad Faizal (2024)
The purpose of this study was to investigate the antecedents factors in customer loyalty among depositors in Tabung Haji, Malaysia in Selangor. This study examines the factor sense of customer satisfaction, service quality, and trust as antecedent factor in customer loyalty among depositors in Tabung Haji, Malaysia in Selangor. A total of 300 respondents were taken based on an online questionnaire that had been successfully collected from Selangor which is a customer loyalty in Tabung Haji, Malaysia. The sampling method used in this study is a non-probability sampling method that makes convenience sampling an option. Data collection for this study was done by researchers using a “Google Form” distributed online. As for the results, all of the independent variables studied in this research had significant relationships with dependent variables. The findings of this research showed that all the hypotheses are accepted. In addition, this study has several limitations to deal with while conducting this research. Therefore, certain recommendations and suggestions have been made that future researchers may find useful in addressing the shortcomings mentioned in this work.